Dialog Antarumat Beragama Perspektif Hadis - Zainudin (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2022)
The Prophet's social life in inter-religious interaction can be seen in the text of the Prophet's hadith, it can be explained that inter-religious dialogue existed at the time of the Prophet. In his social life, the Prophet has practiced religious tolerance with non-Muslims. Interfaith relations at the time of the Prophet were carried out openly and in dialogue. In the hadith of the Prophet there is no interfaith life that can disrupt interfaith relations, except in a state of war caused by interference from non-Muslim parties who attack the Prophet. In the hadiths of the Prophet found several traditions that describe the harmonization and harmony between religious believers between the Prophet and non-Muslims. The existence of the Prophet and non-Muslims having good relations, it shows that the Prophet can protect all parties of different faiths, even though the practice of da'wah or prophetic missions continues to run well, so that between prophetic missions and dialogical life with non-Muslims there is always harmony and remains in harmony.